Prediction of Preeclampsia And Adverse Pregnancy Outcome On The Basis Of Uterine Artery Doppler In Patient With High Clinical Suspicion - Patwa, Prerna Anup; Parihar, Pratapsingh H (International Journal of Psychosocial Rehabilitation, 2020)
Doppler Ultrasonography of Uterine artery is well suited to study preeclampsia and adverse pregnancy outcomes. Routine ANC ultrasonography aids evaluation of foetal well being grossly, in addition uterine artery Doppler helps to find out about the utero-placental circulation which is also important knowing the foetal well being and in turn better pregnancy outcome. Objectives: Analyzing uterine artery Doppler in the suspected cases of preeclampsia. To study correlation between uterine artery Doppler with preeclampsia. Studying the foetal and maternal outcome in patients with preeclampsia. Methodology: In our study, we will include all pregnant females with suspicious preeclampsia who are advised ultrasound and Doppler study for the evaluation with their consent. Colour Doppler imaging will be performed and the waveforms along with resistive Index, Pulsitality Index and Standard deviation is assessed. Images will be obtained from the device and studied for evaluation.